Maturity and quality of carabao mango, mangifera indica, fruits harvested from trees with and without flush. - Dicen, Philip Kenneth (UPHSI, 2004)
A comparison of rate and maturity and quality of fruits from trees with and without flush was examined. Trees with and without flush were identified fruits from these trees were harvested at 110 days after flower induction. Maturity indicators used are the presence of powdery deposits, flotation method, shoulder broadness, percentage weight loss, and peel color index. The presence and the degree of infection from anthracnose and stem end rot, and the external and internal characteristics of the fruits were the basis for the fruit quality. The results showed that there are significant differences in fruits harvested from trees with and without flush using the flotation method and measurement of shoulder broadness. In terms of disease incidence, fruits from tree without flush has lesser disease incidence than fruits from the tree with flush. Fruits from the tree without flush mature faster and have a better resistant to diseases than fruits from the tree with flushes.